Kuliah Kerja Nyata Tematik Periode Ke 1 Di Kelurahan Pematang Gubernur Kecamatan Muara Bangkahulu Kota Bengkulu Tahun 2025 - Dwisari, Hanisyah Herti; Novalia, Tiary; Safitri, Trisna Wulan; Kurniawan, Yogi; Andreani, Inda Andreani; Retni, Retni; Rohani, Tuti; Azissah, Danur (Jurnal Gotong Royong, 2025)
Hypertension and diabetes mellitus are two non-communicable diseases (NCDs) that have a high prevalence in Indonesia. Both diseases often go undiagnosed at an early stage, which can lead to serious complications such as stroke, heart attack and other organ damage. This health situation analysis aims to identify health problems related to hypertension and diabetes mellitus, their contributing factors, and provide recommendations for better management. Based on the 2018 Riskesdas, the prevalence of hypertension in adults in Indonesia reached 34.1%, hypertension often goes undetected because it does not show obvious symptoms in the early stages. Diabetes mellitus has also increased, the prevalence of diabetes mellitus in people aged 15 years and over is 6.9% and most cases are undiagnosed. There were 452 patients with hypertension in the UPTD Puskesmas Muara Bangkahulu in 2023 and an estimated 103 patients with diabetes mellitus in the general clinic at the UPTD Puskesmas Muara Bangkahulu in 2023. After conducting an assessment of residents of RT 27 Pematang Governor village, Muara Bangkahulu sub-district, it was found that some residents had a history of hypertension and diabetes mellitus. Based on the analysis of the health situation, the health priorities that need to be addressed immediately are hypertension problems in the community, especially in RT 27. The problem of diabetes mellitus in the community, especially in RT 27, The solution to the problem from the situation analysis is to conduct a campaign or education about healthy lifestyles, conduct early detection and health checks related to hypertension and diabetes mellitus with the success indicator of the difference in the increase in knowledge before and after counseling using a questionnaire, and it was found that there was a significant change between before and after the counseling was given, namely in hypertension there was an increase in good knowledge from 21% to 74%, while for less criteria there was a change from 79% to 26%. While counselling about diabetes mellitus, the average pre-test knowledge of the elderly about diabetes mellitus before being given counselling about diabetes mellitus is 65 in the sufficient category. Then the average post-test knowledge of the elderly about diabetes after being given counseling about diabetes mellitus is 80 in the good category, so it can be concluded that there is a significant change in knowledge before and after being given counseling.